Effect of Genetic Variation of IL-13 on Airway Remodeling in Bronchial Asthma - Nagashima, Hiromi; Nakamura, Yutaka; Kanno, Hiroyuki; Sawai, Takashi; Inoue, Hiroshi; Yamauchi, Kohei (Allergology International, 2011)
IL-13 is a major stimulator of inflammation and tissue remodeling at sites of Th2 inflammation, and common single-nucleotide polymorphisms in IL13 are associated with allergic phenotypes in several ethnically diverse populations. In particular, IL13Q110 is the non-conservative replacement of a positively charged arginine (R) with a neutral glutamine (Q) at position 110 of IL-13, and as we already know, individuals homozygous for glutamine (Q110/Q110) are strongly associated with asthma and IgE. IL13Q110 has been demonstrated to show that increased allergic inflammation depended on the enhanced IL-13-mediated Th2 effector function. Therefore, we investigated whether Q110/Q110 accelerated the decline in pulmonary function and development of airway remodeling of asthmatic patients in the general population. A total 336 asthmatic subjects living in Japan were recruited, genotyped, and had a pulmonary function test performed on them. To analyze airway inflammation and remodeling, bronchial lavage fluid (BLF) and endobronchial biopsy specimens were examined. Forced expiratory volume in one second (FEV1), %predicted, forced expiratory volume/forced vital capacity ratio, and forced expiratory flow 25-75%, % predicted were significantly decreased in Q110/Q110 compared to R110/R110, and the decline in FEV1 was increased significantly in Q110/Q110 compared to R 110/R110. The concentration of IL-13, IL-23, IL-11, GM-CSF, hyaluronic acid, and CCL8 in BLF were increased in Q110/Q110 compared to R110/R110 and the thickness of the subepithelial layer was thicker. Our study demonstrates that Q110/Q110 increases, at least in part, allergic inflammation and the propensity for airway remodeling, thus resulting in low lung function.